How response biases affect the factor structure of Big Five personality questionnaires - Morales-Vives, Fabia; Lorenzo-Seva, Urbano; Vigil-Colet, Andreu (Anales de Psicología / Annals of Psychology, 2017)
Several studies have shown that personality self-reports may be affected by response biases, and that this may have consequences on their factor structure, especially in samples with little education or in adolescents. The current study aims to understand the effect of social desirability and acquiescence on the factor structure of three questionnaires based on the Five Factor Model of personality: the Big Five Inventory, the Five Factor Personality Inventory and the Overall Personality Assessment Scale. The data was analysed using a new method that removes the effects of both social desirability and acquiescence from the inter-item correlation matrix used for factor analysis. These effects were assessed in a sample of 392 university students, which contained no individuals with low educational levels, children or adolescents. The results showed that, even in samples with no individuals with low educational levels, controlling for social desirability and acquiescence led to a simpler factor structure that is more congruent with the theoretical solution expected from the five factor model. It also seems that in the domain of inventories based upon the five factor model, this effect may be specially due to acquiescence.